2017
DOI: 10.1016/j.tjog.2015.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Transcervical double-balloon catheter as an alternative and salvage method for medical termination of pregnancy in midtrimester

Abstract: There was no significant additional benefit of using a double-balloon catheter in midtrimester termination of pregnancy, although the technique was considered simple and generally well-tolerated. Placing a transcervical double-balloon catheter could be the primary method, or one of the alternative medical methods if the patient and/or obstetrician prefers no operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The patient with comprehensive-induce methods to terminate the pregnancy in the mid-trimester had more complications of prenatal hemorrhage (30% vs 0%), postpartum hemorrhage (50.0% vs 2.4%), puerperal infection (80.0% vs 2.4%), the main reason is the patients with prenatal hemorrhage or immature cervical conditions [29] .…”
Section: Discussionmentioning
confidence: 99%
“…The patient with comprehensive-induce methods to terminate the pregnancy in the mid-trimester had more complications of prenatal hemorrhage (30% vs 0%), postpartum hemorrhage (50.0% vs 2.4%), puerperal infection (80.0% vs 2.4%), the main reason is the patients with prenatal hemorrhage or immature cervical conditions [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Zhang X et al [15] analyzed 1,260,684 births from the surveillance system in Zhejiang province, China, and found that the rate of birth defects during 2013, 2015, and 2017 was 245.95, 264.86, and 304.36 per 10,000 births, respectively, and there was age-related anomalies after the release of China's new two-child policy. There were many clinical problems during induced labor need to be solved, especially complete placenta previa [16], and immature cervical condition [2]. More and more women in developing countries choose to postpone pregnancy [17], and studies have found an association between elder pregnant women and a high risk of chromosomal abnormalities, miscarriages and preterm birth with gestation of less than 34 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have evaluated the effectiveness of these devices by comparing them with prostaglandins, and have reported that they are equally effective, and the incidence of tachycardia is lower than that of prostaglandins [9]. Placing a transcervical DBC can be the primary method, or one of the alternative medical methods if the patient and/or obstetrician prefers not to conduct surgical operation [2]. DBC are commonly used for cervical ripening to induce labor with and without prior cesarean section in term [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations